UI/UX Design on Prototype Attendance Using the Design Thinking Method - Shandy Putra Gautama; Septi Fajarwati; Aulia Hamdi (Universitas Amikom Purwokerto, 2023)
Presence is a data collection activity to determine the number of attendance. Presence is a process of activities that is often carried out even every day by many corporate agencies or schools and colleges. One of the institutions that use presence is a school. Several schools have implemented attendance systems. But there are a number of schools that still apply manual attendance where employees or teachers must sign the attendance sheet, one of which is SMK Mpu Tantular Kemranjen which still applies attendance manually. Obstacles experienced from using manual attendance are that there is often a mismatch between attendance by teachers and staff employees in the field with notes made in the TU section and sometimes there are teachers and staff employees who leave absences. Therefore it is necessary to make a UI/UX design design for the attendance application that is appropriate for the attendance process for teachers and staff employees at SMK Mpu Tantular Kemranjen. This study uses the Design Thinking method with 5 stages, namely Emphatize, Define, Ideate, Prototype, and Test. The results of this study are in the form of a UI/UX prototype design for presence applications that suit user needs.